(untitled) (Experimental biology, 2023)
In this study, the ecological testing of 139 accessions of the winter wheat collection from Central Asia was conducted on the field plots of the Kazakh Research Institute of Agriculture and Plant Industry (Almaty region, Southeast Kazakhstan) and Krasnovodopad Breeding Station (Turkestan region, South Kazakhstan) during 2020-2021 and 2021-2022 growing seasons. The collection was analyzed using 12 traits: heading date, seed maturation date, vegetation period, plant height, peduncle length, spike length, number of productive spikes, number of kernels per spike (NKS), weight kernel per spike, weight kernel per plants, thousand kernel weight (TKW) and yield per square meter (YM2). The Pearson correlation index showed positive correlations between yield-related traits in the two studied regions. The average YM2 value of 107 and 134 accessions exceeded the check cultivars in Almaty (Zhetisu) and Turkestan (Pamyat 47) regions, respectively. Seven cultivars (Karaspan, Mars 1, Pamyat, Dank, Zhamin, KYIAL, and Talimi) were revealed to be highly productive for three traits (NKS, TKW and YM2) in two regions. The analysis of variance showed that genotype × environment interaction affected the studied traits of the winter wheat collection from Central Asia under Kazakhstan’s conditions. The results of this research will be used for further studies related to adaptation and productivity of winter wheat in the breeding program for the selection of best candidate lines and genome-wide association study for yield and yield-related traits in winter wheat.